107 Effects of IL-2 and IL-15 on the proliferative and antitumor capacities of allogeneic CD20 CAR-engineered γδ T cells in a 3D B cell lymphoma spheroid assay. (9th November 2020) - Bai, Lu; Nishimoto, Kevin; Turkoz, Mustafa; Herrman, Marissa; Romero, Jason; Satpayev, Daulet; Abbot, Stewart; Hayes, Sandra; Brodey, Mary
Abstract : Background: Autologous chimeric antigen receptor (CAR) T cells have been shown to be efficacious for the treatment of B cell malignancies; however, widespread adoption and application of CAR T cell products still face a number of challenges. To overcome these challenges, Adicet Bio is developing an allogeneic γδ T cell-based CAR T cell platform, which capitalizes on the intrinsic abilities of Vδ1 γδ T cells to recognize and kill transformed cells in an MHC-unrestricted manner, to migrate to epithelial tissues, and to function in hypoxic conditions. To gain a better understanding of the requirements for optimal intratumoral CAR Vδ1 γδ T cell activation, proliferation, and differentiation, we developed a three-dimensional (3D) tumor spheroid assay, in which tumor cells acquire the structural organization of a solid tumor and establish a microenvironment that has oxygen and nutrient gradients. Moreover, through the addition of cytokines and/or tumor stromal cell types, the spheroid microenvironment can be modified to reflect hot or cold tumors. Here, we report on the use of a 3D CD20+ Raji lymphoma spheroid assay to evaluate the effects of IL-2 and IL-15, positive regulators of T cell homeostasis and differentiation, on the proliferative and antitumor capacities of CD20 CAR Vδ1 γδ T cells. Methods: Molecular, phenotypic, and functional profiling were performed to characterize the in vitro dynamics of the intraspheroid CD20 CAR Vδ1 γδ T cell response to target antigen in the presence of IL-2, IL-15, or no added cytokine. Results: When compared to no added cytokine, the addition of IL-2 or IL-15 enhanced CD20 CAR Vδ1 γδ T cell activation, proliferation, survival, and cytokine production in a dose-dependent manner but were only able to alter the kinetics of Raji cell killing at low effector to target ratios. Notably, differential gene expression analysis using NanoString nCounter® Technology confirmed the positive effects of IL-2 or IL-15 on CAR-activated Vδ1 γδ T cells as evidenced by the upregulation of genes involved in activation, cell cycle, mitochondrial biogenesis, cytotoxicity, and cytokine production. Conclusions: Together, these results not only show that the addition of IL-2 or IL-15 can potentiate CD20 CAR Vδ1 γδ T cell activation, proliferation, survival, and differentiation into antitumor effectors but also highlight the utility of the 3D spheroid assay as a high throughput in vitro method for assessing and predicting CAR Vδ1 γδ T cell activation, proliferation, survival, and differentiation in hot and cold tumors.